HfMnSb2: A Metal‐Ordered NiAs‐type Pnictide with a Conical Spin Order. (29th June 2016) - Murakami, Taito; Yamamoto, Takafumi; Tassel, Cédric; Takatsu, Hiroshi; Ritter, Clemens; Ajiro, Yoshitami; Kageyama, Hiroshi
Abstract: The NiAs‐type structure is one of the most common structures in solids, but metal order has been almost exclusively limited to chalcogenides. The synthesis of HfMnSb2 is reported with a novel metal‐ordered NiAs‐type structure. HfMnSb2 undergoes a conical spin order below 270 K, in marked contrast to conventional magnetic order observed in NiAs‐type pnictides. We argue that the layered arrangement of Hf and Mn makes it a quasi 2D magnet, where the Mn layers with localized magnetic moments (Mn 2+ ; S =5/2) can interact only through RKKY interactions, instead of metal–metal bonding that is otherwise dominant for typical NiAs‐type pnictides. This result suggests that controlling order–disorder in NiAs‐type pnictides enables a study of 2D‐to‐3D crossover behavior in itinerant magnetic system.